Non-invasive Approaches for the Diagnosis of Autoimmune/Autoinflammatory Skin Diseases—A Focus on Psoriasis and Lupus erythematosus - Berekméri, Anna; Tiganescu, Ana; Alase, Adewonuola A.; Vital, Edward; Stacey, Martin; Wittmann, Miriam (Frontiers in Immunology, 2019)
The traditional diagnostic gold standard for inflammatory skin lesions of unclear aetiology is dermato-histopathology. As this approach requires an invasive skin biopsy, biopsy processing and analysis by specialised histologists, it is a resource intensive approach requiring trained healthcare professionals. In many health care settings access to this diagnostic approach can be difficult and outside emergency cases will usually take several weeks. This scenario leads to delayed or inappropriate treatment given to patients. With dramatically increased sensitivity of a range of analysis systems including mass spectrometry, high sensitivity, multiplex ELISA based systems and PCR approaches we are now able to “measure” samples with unprecedented sensitivity and accuracy. Other important developments include the long-term monitoring of parameters using microneedle approaches and the improvement in imaging systems such as optical coherence tomography. In this review we will focus on recent achievements regarding measurements from non-invasive sampling, in particular from plucked hair and skin tape-strips which seem well suited for the diagnosis of lupus erythematosus and psoriatic inflammation, respectively. While these approaches will not replace clinical observation – they can contribute to improved subgroup diagnosis, stratified therapeutic approaches and have great potential for providing molecular and mechanistic insight in to inflammatory skin diseases